<span>(3x-4)+(x+3)^2
= 3x - 4 + x^2 + 6x + 9 .........(expand using (a+b)^2 = a^2 + 2ab + b^2)
= x^2 + 9x + 5 ..........(combine like terms and simplify)
hope that helps</span>
Answer:
Slopem=74
As a decimal:
m = 1.75
Step-by-step explanation:
Answer:
t = 12h
Step-by-step explanation:
t = total
h = hours
Let x=ab=ac, and y=bc, and z=ad.
Since the perimeter of the triangle abc is 36, you have:
Perimeter of abc = 36
ab + ac + bc = 36
x + x + y = 36
(eq. 1) 2x + y = 36
The triangle is isosceles (it has two sides with equal length: ab and ac). The line perpendicular to the third side (bc) from the opposite vertex (a), divides that third side into two equal halves: the point d is the middle point of bc. This is a property of isosceles triangles, which is easily shown by similarity.
Hence, we have that bd = dc = bc/2 = y/2 (remember we called bc = y).
The perimeter of the triangle abd is 30:
Permiter of abd = 30
ab + bd + ad = 30
x + y/2 + z =30
(eq. 2) 2x + y + 2z = 60
So, we have two equations on x, y and z:
(eq.1) 2x + y = 36
(eq.2) 2x + y + 2z = 60
Substitute 2x + y by 36 from (eq.1) in (eq.2):
(eq.2') 36 + 2z = 60
And solve for z:
36 + 2z = 60 => 2z = 60 - 36 => 2z = 24 => z = 12
The measure of ad is 12.
If you prefer a less algebraic reasoning:
- The perimeter of abd is half the perimeter of abc plus the length of ad (since you have "cut" the triangle abc in two halves to obtain the triangle abd).
- Then, ad is the difference between the perimeter of abd and half the perimeter of abc:
ad = 30 - (36/2) = 30 - 18 = 12
Answer:
17,19,21
Step-by-step explanation:
let the first odd number be "x"
formular : (x)+(x+2)+(x+4).
3x+6=57
3x=57-6
3x=51
x=51/3
x=17
apply the formular.
17,(17+2),(17+4)
17,19,21.